Answer:
A.) 2√6 + 4
Explanation:
The reason for the direction to use a conjugate to rationalize the denominator is that multiplying by the conjugate lets you take advantage of the factoring of the difference of squares:
(a +b)(a -b) = a² -b²
When "a" or "b" involves a square root, this will eliminate the radical.
So, you have ...
![(2√(2))/(√(3)-√(2))=(2√(2)(√(3)+√(2)))/((√(3)-√(2))(√(3)+√(2)))\\\\=(2√(2\cdot 3)+2√(2\cdot 2))/(3-2)=2√(6)+4](https://img.qammunity.org/2020/formulas/mathematics/college/lx2ohnex97a1xdyxb5uumgtue31putt1sp.png)